Konseling Individu dengan Pendekatan Dakwah Fardiyah untuk Meningkatan Rasa Percaya Diri Berbusana Muslimah - Kusnadi, Aura Siti Aulia; Arifin, Isep Zaenal; Muttaqin, Zaenal (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
This paper aims to determine the condition of self-confidence, the process and the results of individual counseling services with the dakwah fardiyah approach to increase the confidence of students in Muslim women's clothing. The method in this study uses a qualitative phenomenological method where data collection is through participatory observation and in-depth interviews with class X language students and BK teachers at SMA Negeri 6 Garut. The results of the study found that the condition of students' self-confidence in Muslim women's clothing was still less marked by the presence of students who had not used Muslim clothing. There are three stages in the individual counseling service process, namely the initial stage, the working stage, and the final stage. The results of individual counseling services with the fardiyah da'wah approach can be said to be effective, it can be seen that there is an increase in students' self-confidence in dressing Muslim women in the school environment and in everyday life.